2017
DOI: 10.1002/cncr.30698
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness practice reduces cortisol blunting during chemotherapy: A randomized controlled study of colorectal cancer patients

Abstract: Background The objective of this randomized clinical experiment was to test the influence of a mindfulness meditation practice, when delivered during one session of active chemotherapy administration, on acute salivary cortisol response as a marker of the neuroendocrine system activity in cancer patients. Methods A mindfulness, attention control, or resting exposure was assigned to N=57 English- or Spanish- speaking colorectal cancer patients at one county oncology clinic and one university oncology clinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 51 publications
0
49
0
1
Order By: Relevance
“…Along those lines, among samples of military veterans with PTSD (Bergen-Cico et al, 2014), substance use disorders patients (Marcus et al, 2003), cancer patients and their caregivers (Lengacher et al, 2012), and healthy adults (Brand et al, 2012), participants experienced significant reductions in CAR levels from pre- to post-training. Alternatively, among samples of patients currently receiving chemotherapy for colorectal cancer (Black et al, 2017) and who completed treatment for breast cancer (Matousek et al, 2011), CAR showed a prolonged increase after awakening at the post-training assessment. In these studies, authors suggest that given the prolonged traumatic nature of cancer and its treatment, it may have resulted in participants exhibiting a blunted CAR at pre-training, and therefore MT would be expected to increase, and not decrease, CAR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along those lines, among samples of military veterans with PTSD (Bergen-Cico et al, 2014), substance use disorders patients (Marcus et al, 2003), cancer patients and their caregivers (Lengacher et al, 2012), and healthy adults (Brand et al, 2012), participants experienced significant reductions in CAR levels from pre- to post-training. Alternatively, among samples of patients currently receiving chemotherapy for colorectal cancer (Black et al, 2017) and who completed treatment for breast cancer (Matousek et al, 2011), CAR showed a prolonged increase after awakening at the post-training assessment. In these studies, authors suggest that given the prolonged traumatic nature of cancer and its treatment, it may have resulted in participants exhibiting a blunted CAR at pre-training, and therefore MT would be expected to increase, and not decrease, CAR.…”
Section: Discussionmentioning
confidence: 99%
“…MT has garnered significant empirical support in lab, clinical, and community-based research, evincing outcomes such as reduced aggression (Fix and Fix, 2013; Kelley and Lambert, 2012; Zoogman et al, 2014) and anger (Peters et al, 2015; Singh et al, 2014). MT has also been shown to reduce stress reactivity, including reductions in pre- to post-training CAR levels (Brand et al, 2012; Lengacher et al, 2012; Marcus et al, 2003); however, others (Black et al, 2017; Matousek et al, 2011) have found prolonged increase in CAR after awakening at the post-training assessment. MT may therefore exert its effect by helping to normalize CAR, increasing it in samples with dampened stress reactivity and reducing it in those with heightened stress reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study of 30 postmenopausal women, salivary and urinary excretion of cortisol following a metabolic stressor (oral glucose consumption) was higher in 16 long-term practitioners of transcendental meditation when compared with 14 non-meditators, which may reflect improved endocrine regulation in response to metabolic challenge [41]. In a randomized controlled trial of 57 patients with colorectal cancer, a single mindfulness meditation practice delivered during active chemotherapy administration resulted in increased cortisol reactivity, suggesting that mindfulness practice can reduce the blunting of neuroendocrine profiles typically observed in cancer patients and supporting the use of mindfulness in oncology [42]. These studies collectively indicate that meditation influences the regulation of the HPA axis, which may reflect decreased stress levels among meditators.…”
Section: Meditation Influences the Hypothalamic-pituitary-adrenal (Hpmentioning
confidence: 91%
“…For the cases other than cancer, we can mention the study of Laurent et al who reported that mindfulness, during a conflict discussion, could reduce the effects of negative partner behaviors on neuroendocrine stress responses (29). For the people suffering from cancer, some studies provide the evidence that cancer survivors with higher levels of MBIs may be buffered from deleterious changes in cortisol secretion (30). To the best of our knowledge, some research scales used to measure cortisol, the exact time of sampling, patients' condition, adherence to intervention, study limitations and large unexplained variability.…”
Section: Discussionmentioning
confidence: 99%